The Difference in The Effect Between The Oxygenated and Mineral Water on The O2 Saturation And Urine pH - Ellyana, Naila Shulya; Sarosa, Hadi; Hussaana, Atina (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2011)
Background: During exercise, oxygen decreases due to acidosis leading the production acid urine by kidney. Oxygenated water having capability to absorb more oxygen compared to mineral water is used to meet the oxygen need during exercise. This study investigated the effect of oxygenated water and mineral water on the O2 saturation and urine pH.Design and method: In this crossover study, 46 subjects were randomly assigned to either oxygenated water or mineral water for 24 hours followed by a crossover to the other regimen for an additional 24 hours of treatment. After 100 m sprint running for 20 minutes, the oxygen saturation and urine pH of the subjects were assessed.Result:The mean oxygen saturation before and after the treatment of oxygenated water were 96.78±1.32 and 97.61±0.93 respectively. The mean oxygen saturation before and after the mineral water treatment was 97.35±0.85 and 97.01±1.04 respectively. The urine pH after the administration of oxygenated water and mineral water were 6.643±0.69 and 6.585±0,58 respectively. Wilcoxon test resulted in no significant difference in pH after the treatment of oxygenated water and mineral water (p=0.498). Urine pH after the treatment of oxygenated water was found to be higher compared to that of mineral water.Conclusion: the oxygenated water increases the O2 saturation and urine pH compared to mineral water (Sains Medika, 3(2):162-167).